2022
DOI: 10.1177/10748407221097460
|View full text |Cite
|
Sign up to set email alerts
|

Stepparent–Child Relationships and Child Outcomes: A Systematic Review and Meta-Analysis

Abstract: An inclusive conceptualization of “family” can enable family-serving systems and professionals to leverage high-quality family relationships, wherever they are found, to support the health and well-being of individuals. Stepfamilies are an especially common family form with distinct needs and experiences, and stepparent–child relationships can take on a variety of functions with implications for family stability and individual well-being. The purpose of this systematic review and meta-analysis was to synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 83 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…Normative‐adaptive perspectives that shed light on resilience in complex families are the foundation of my work. Efforts to highlight the strengths of stepfamilies (and of non‐nuclear family forms more broadly) remain necessary, and those who are committed to these efforts should know that they are in good company (see Acosta, 2021; Adler‐Baeder & Higginbotham, 2020; Beckmeyer et al, 2020; Bergeson et al, 2020; Bermea et al, 2020; Braithwaite et al, 2018; Ganong & Coleman, 2018; Jensen, 2022; Oliver‐Blackburn et al, 2022; Papernow, 2018; Petren & Ferraro, 2022; Russell et al, 2022; van Eeden‐Moorefield & Pasley, 2013; Waldron et al, 2018). In my journey of working toward a more holistic understanding of stepfamily life that challenges deficit perspectives of family complexity, another theoretical home also has been foundational to my thinking and scholarship: feminist theory.…”
Section: Part Ii: Professional Perspectivesmentioning
confidence: 99%
“…Normative‐adaptive perspectives that shed light on resilience in complex families are the foundation of my work. Efforts to highlight the strengths of stepfamilies (and of non‐nuclear family forms more broadly) remain necessary, and those who are committed to these efforts should know that they are in good company (see Acosta, 2021; Adler‐Baeder & Higginbotham, 2020; Beckmeyer et al, 2020; Bergeson et al, 2020; Bermea et al, 2020; Braithwaite et al, 2018; Ganong & Coleman, 2018; Jensen, 2022; Oliver‐Blackburn et al, 2022; Papernow, 2018; Petren & Ferraro, 2022; Russell et al, 2022; van Eeden‐Moorefield & Pasley, 2013; Waldron et al, 2018). In my journey of working toward a more holistic understanding of stepfamily life that challenges deficit perspectives of family complexity, another theoretical home also has been foundational to my thinking and scholarship: feminist theory.…”
Section: Part Ii: Professional Perspectivesmentioning
confidence: 99%
“…When the relationship between the other parent and the stepparent is poor, the child might refrain from bonding with the stepparent following the loyalty conflict they may feel toward their other parent (Ganong et al, 2011). Focusing on stepfamilies with adult children, prior research found a positive association between the two dyads (Hornstra et al, 2020;2022). We expect a higher relationship quality of the biological parent-child dyad (H1-Dyad A), of the stepcouple dyad (H2-Dyad B), and of the stepparent-the other parent dyad (H3-Dyad C) to associate with higher stepparent-child relationship quality (Dyad D).…”
Section: Dyadic Family Relationshipsmentioning
confidence: 99%
“…As a result, some stepfamilies might lack the motivation to form strong stepparent-child bonds (Ganong & Coleman, 2017). Despite the fragility of this dyad, building positive stepparent-child relationships has many benefits for children, such as improving their psychological well-being (Jensen, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors demonstrate that youth in several diverse family structures are less likely to have consistent places to go for health care services; although when they do seek services, they are more likely to have time alone to speak with a health care provider privately compared with peers in nuclear family structures. Using meta-analytic procedures, Jensen (2022) provides an overarching view of factors that promote stepchild health and well-being. These findings demonstrate the critical role of stepparent–stepchild relationships (family members who are not always appropriately included in health care services, and sometimes pushed out; Kelly & Ganong, 2011; Toelen et al, 2022).…”
Section: The Special Issue On Supporting Structurally Diverse Familiesmentioning
confidence: 99%